Multi-criteria evaluation approach to coastal vulnerability index development at Penang Coast / Nur Shahira Shahlan - Shahlan, Nur Shahira (2024)
Most coastal regions throughout the world are suffering because of climate change. Sea Level Rise (SLR) has exposed coastal regions to a variety of risks, including inundation and erosion, which have a negative impact on coastal areas. The main objective of this research is to analyze the Coastal Vulnerability Index (CVI) approaches from Tanjung Tokong, Tanjung Bungah, Batu Ferringhi, Teluk Bahang, and Monkey Beach on the Penang coast. This CVI includes six parameter that is coastal geomorphology, coastal slope, rate of erosion and accretion, rate of sea level rise, mean tidal range, and land use land cover (LULC). Based on the rating values of the following parameter, the vulnerability levels for five management units along the Penang coast are grouped into five vulnerability rankings: very low, low, moderate, high, and very high. According to the fïndings, Batu Ferringhi and Tanjung Tokong was classified as having a very high and high vulnerability rating of 90% and 70%, respectively. Meanwhile, the Monkey Beach and Teluk Bahang coastline is only 10% and 30% which is very low and low vulnerable, respectively. Other than that, CVI values of 50% signify the moderate vulnerability rate category for Tanjung Bungah. Finally, this study presents a CVI map of Penang shoreline that decision makers and relevant authorities may use to implement mitigation and adaptation policies to address the implications of climate change on coastal regions.